Experiences of healthcare workers who faced physical workplace violence from patients or their relatives in Nepal: a qualitative study - Mukesh Adhikari; Dinesh Timalsena; Kalpana Chaudhary (BMJ Publishing Group, 2024)
Introduction Workplace violence (WPV) against healthcare workers (HCWs) has become a global concern. Our aim was to investigate the firsthand experience of HCWs who faced physical WPV from patients or their relatives in Nepal and to identify the factors that contribute to WPV, its consequences, as well as recommendations from HCWs on preventing and managing WPV in healthcare settings.Methods We conducted semistructured in-depth interviews of 12 HCWs who faced physical WPV from patients or their relatives in the last 2 years in Nepal. We recruited participants by announcing volunteer participation on social media and reaching out to HCWs who had experienced WPV through a review of national news archives. All interviews were conducted between September and November 2022. We analysed the data using a hybrid thematic analysis.Results Most participants were male (9/12). The average age of participants was 31.6 years with an average experience of 8.3 years. We generated three domains: (1) factors contributing to WPV, (2) response to WPV and (3) recommendations. Within these three domains, we identified a total of nine themes: two themes (proximal and distal factors) under domain 1, four themes (personal response, hospital administration response, police response and other responses) under domain 2 and three themes (recommendations at personal, organisational and policy level) under domain 3. We found that physical WPV against HCWs is multifactorial. Most HCWs did not receive expected support from hospital and police administration. They had a wide range of recommendations at personal, organisational and policy level. The most important recommendation was to ensure safety and security of HCWs.Conclusions This qualitative study showed that experiences of HCWs who faced physical WPV in Nepal were traumatic. The concerned stakeholders should carefully consider the recommendations from HCWs to establish a safe, secure and supportive working environment.